Membangun Character Building Peserta Didik Mts Hidayatul Mubtadiin Dan Relevasinya Bagi Pengembangan Pendidikan Agama Islam - Rina Setyaningsih (At-Ta'dib, 2024)
Character building or character education is an important discussion in the world of education. This review can be calculated and started from the movement of degradation or deterioration of morals and morals in the midst of society with various varieties and types. Character education or often known as character building among students in particular is very much needed. As a result, character education among students or school students is the beginning of early education that needs to be carried into the future. Thus, the value of Islamic religious education needs to play an active role in improving and developing character in the student and school environment. So the attitude of responsibility can be used as a form of manifestation that Islamic religious education in the Hidayatul Mubtadiin MTs environment must continue to be maximised in the formation of student character. The efforts made in this research method are through a qualitative approach. As an approach whose purpose is to obtain data, symptoms and phenomena of how the application of character education is built in concentration or carried out by Islamic Religious Education Teachers in Hidayatul Mubtadiin MTs students, Jati Agung South Lampung. This is done by how habituation and application of good behaviour or with noble character. Providing habituation of greetings, smiles and greetings as a fruit of student manners at school. Also provide religious guidance to deepen religious understanding that is relevant to character education teaching materials in the school environment.